An assessment of the Europeans’ Bank bailout policies since the global financial crisis and a proposal for reforms: a comparison with the US experience - Hryckiewicz, A; Kryg, N; Tsomocos, D (European Liberal Forum, 2023)
Europe still has a lot to learn from the events of the Global Financial Crisis (GFC) of 2008 as it continues with reforms of its bank resolution ecosystem. Through a comparison of the bailout mechanisms used in Europe and the United States during the GFC, we show that the US bank bailout approach appears to have been much more successful than the European one. The separation of governance functions from management functions and the nature of voting rights have incentivised the US Treasury to actively intervene in the distressed banks by imposing critical changes, for example a change of CEO or affecting the board compensation. In addition, such US Treasury behaviour has also disciplined other banks to implement the necessary restructuring changes to avoid government intervention. In turn, the European bailout approach has supported government passiveness in the governance functions and its greater involvement in bank business. As a result, we have noticed a significant increase in board compensation at nationalised banks, and no significant restructuring changes. Our findings call for bailout mechanisms incentivising the resolution authority playing an active role in the governance functions at distressed banks without significant involvement in bank business. We also opt for time-constrained intervention.